2010
DOI: 10.3844/ajbbsp.2010.204.212
|View full text |Cite
|
Sign up to set email alerts
|

Impact of L-Carnitine and Cinnamon on Insulin-Like Growth Factor-1 and Inducible Nitric Oxide Synthase Gene Expression in Heart and Brain of Insulin Resistant Rats

Abstract: Problem statement: Evaluate the effects of daily administration of L-carnitine and cinnamon extract for two weeks on the expression of Insulin-like Growth Factor-1 (IGF-1) and inducible Nitric Oxide Synthase (iNOS) genes in cardiac and brain tissues of rats with Insulin Resistance (IR). Approach: Rats were divided into 4 groups (8 animals each): Group (1) rats fed control diet (60% starch) as control while groups (2, 3 and 4) fed high fructose diet (60% fructose). At the beginning of the 3rd week of feeding, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Insulin resistance induced by a high fructose diet in rats is well documented [3,5,23,28] and has been established in the present study. The degree of insulin resistance was higher in HFD1 and HFD2 groups as indicated by the significant elevation of serum insulin levels and HOMA-IR.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Insulin resistance induced by a high fructose diet in rats is well documented [3,5,23,28] and has been established in the present study. The degree of insulin resistance was higher in HFD1 and HFD2 groups as indicated by the significant elevation of serum insulin levels and HOMA-IR.…”
Section: Discussionsupporting
confidence: 69%
“…Insulin resistance occurs at multiple levels in cells, from the cell surface to the nucleus, including insulin receptor desensitization and suppression of IRS protein and functionality, all of which can result from inhibition of IRS1 and IRS2 [22]. Previous studies confirmed that the high-fructose diet induces insulin resistance and oxidative stress in rat tissues [3,5,23,24]. Rats fed high-fructose diet showed elevated levels of serum ALT and AST, the specific markers of hepatocellular injury [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies proved the induction of insulin resistance by feeding rats with HFD (Abd El-Wahab, Mohamed, El Sayed, & Bauomy, 2017;Mahfouz, Ghanem, & Mohamed, 2009;Mohamed, 2010;Shawky, Shehatou, Abdel Rahim, Suddek, & Gameil, 2014) and was established in the current study. Feeding rats with HFD for 1 and 2 months (HFD1 and HFD2, respectively) increased the hepatic insulin insensitivity as indicated by the significant elevation of serum insulin and HOMA-IR.…”
Section: Discussionmentioning
confidence: 52%
“…Although extensive studies have been performed investigating the effects of fructose-induced IR on various organs (Mohamed 2010;Ghanem 2010), data on lens integrity and composition in this rat model are lacking (Balasaraswathi et al, 2008). Therefore, the present study was undertaken to assess the effects of administration of either L-carnitine or cinnamon extract on soluble lens crystalline, oxidative stress and protein bound sugar in rats fed high fructose diet.…”
Section: Introductionmentioning
confidence: 99%